2022
DOI: 10.1038/s41598-022-12421-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of short-term particulate matter exposure with suicide death among major depressive disorder patients: a time-stratified case-crossover analysis

Abstract: There is growing evidence that suggests a potential association between particulate matter (PM) and suicide. However, it is unclear that PM exposure and suicide death among major depressive disorder (MDD) patients, a high-risk group for suicide. We aimed to assess the effect of short-term exposure to PM on the risk of suicide in MDD patients who are at high risk for suicide. We investigated the risk of suicide among 922,062 newly-diagnosed MDD patients from 2004 to 2017 within the Korean National Health Insura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Individuals exposed to PM show several notable features, such as impaired brain development, cognitive deficits, inflammation in the blood-brain barrier (BBB), and the accumulation of neurotoxic protein aggregates. [8] The exposure of brain tissue to PM has a negative effect on the central nervous system (CNS) and can cause dementia, [10] stroke, [11] depression, [12] and schizophrenia. [13] To investigate PM toxicity, 2D culture systems and animal models have been widely used.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals exposed to PM show several notable features, such as impaired brain development, cognitive deficits, inflammation in the blood-brain barrier (BBB), and the accumulation of neurotoxic protein aggregates. [8] The exposure of brain tissue to PM has a negative effect on the central nervous system (CNS) and can cause dementia, [10] stroke, [11] depression, [12] and schizophrenia. [13] To investigate PM toxicity, 2D culture systems and animal models have been widely used.…”
Section: Introductionmentioning
confidence: 99%
“…The neurotoxic effects of air pollution can be particularly dangerous to vulnerable populations such as people with mental illnesses. In patients with major depressive disorder, a high-risk group for suicide, there was an association between short-term exposure to PM and suicide, and a clear dose-response relationship between short-term exposure to PM and suicide-related death was confirmed [ 23 ]. Furthermore, an association has been reported between long-term PM exposure and suicide in patients with physical or mental diseases, and a dose-response relationship has been confirmed [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified an association between PM and suicide stratified by sex and age group. Compared to men, the association between PM and suicide was stronger in women [ 16 , 23 ]. Although no significant association in individuals aged 20–39 years was found, in those aged 40 years or older, the suicide risk tended to increase when both particulate matter ≤ 10 μm in diameter (PM 10 ) and particulate matter ≤ 2.5 μm in diameter (PM 2.5 ) concentrations increased [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Air pollution, particularly exposure to fine particulate matter (PM2.5) and nitrogen oxides (NOx), has been associated with depression in youth [7], adults in the general population [8,9], women in the post-partum period [10,11] and the elderly [12]. Exposure to these forms of air pollution has also been associated with worse outcomes in patients with depression, such as suicide [13] and increased use of mental health services [14].…”
Section: Introductionmentioning
confidence: 99%